2018
DOI: 10.3847/1538-3881/aae310
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Blended K2 Photometry: Determining the Planetary Host Star

Abstract: The presence of companion stars, whether bound or unbound, make correct identification of the planetary hosting star difficult when a planet has been detected through a photometrically blended transiting event. We present an approach that uses a combination of light curve analysis and stellar modeling to disentangle 8 K2 photometrically blended binary systems that have either a confirmed or suspected planet to identify the probable host star. The key to our approach is the use of the mean stellar density, calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
5
2
Order By: Relevance
“…Figure 7 shows the primary host star probability as a function of the the binary magnitude difference. While we do not see the strong trend found by Payne et al (2018), where the host component in equal brightness pairs were uncertain due to the similarity in temperature and density, the equal brightness systems in our sample do have slightly lower primary host probabilities that unequal brightness pairs. Furthermore, the systems with faint secondaries (Δm 4 mag) are even more likely to have a primary star host (89%), as seen in Figure 7.…”
Section: Overall Resultscontrasting
confidence: 90%
See 3 more Smart Citations
“…Figure 7 shows the primary host star probability as a function of the the binary magnitude difference. While we do not see the strong trend found by Payne et al (2018), where the host component in equal brightness pairs were uncertain due to the similarity in temperature and density, the equal brightness systems in our sample do have slightly lower primary host probabilities that unequal brightness pairs. Furthermore, the systems with faint secondaries (Δm 4 mag) are even more likely to have a primary star host (89%), as seen in Figure 7.…”
Section: Overall Resultscontrasting
confidence: 90%
“…We calculated the mean stellar density for each component (ρ 1 , ρ 2 , ρ 3 ) following Equations (8)-( 11) in Payne et al (2018), which correct the observed transit depth for the flux contamination from the other components. For example, if the planet orbits the primary star in a binary system, the primary's stellar density is…”
Section: Observed Stellar Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Seager & Mallén-Ornelas (2003) derived a method to determine the stellar density of a planet host star using the transit geometry, which can be extended to planet hosts in multistar systems if the transit depth is corrected for the flux contribution of each component. Payne et al (2018) used this method to identify the planet host star in 8 K2 binary systems and found that the brighter primary star was more likely to host the planet in 5 out of 8 systems. They also found that systems with fainter companions were more likely to have primary host stars.…”
Section: Introductionmentioning
confidence: 99%